Implementation of a Differentiated Project-Based Learning Model to Improve Students' Scientific Process Skills and Scientific Attitudes - Nadila Qothrun Nada Nada (Phenomenon : Jurnal Pendidikan MIPA, 2025)
This study aims to implement a differentiated Project-Based Learning (PjBL) model to improve students' science process skills and scientific attitudes in the topic of renewable energy. A quasi-experimental method with a pretest-posttest control group design was applied. The experimental class was taught using the differentiated PjBL model, while the control class used conventional PjBL. Instruments included open-ended tests to assess science process skills and Likert-scale questionnaires to evaluate scientific attitudes. The results showed a significant improvement in all science process skill indicators and scientific attitudes in the experimental class compared to the control group. Skills such as observing, questioning and predicting, conducting investigations, processing and analyzing data and information, evaluating and reflecting, as well as communicating results improved evenly across the board. Regression analysis indicated that science process skills positively influenced scientific attitudes, contributing 11.8% of the variance. These findings highlight the effectiveness of differentiated PjBL in offering more personalized and contextual learning experiences that develop both cognitive and affective student outcomes. Physics teachers are encouraged to integrate this model into classroom practice and to enhance their competence in designing student-centered project learning. Future studies may explore its application across different subjects and education levels to broaden its impact.